2017
DOI: 10.1186/s13071-017-2240-3
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput colorimetric assay for detection of Schistosoma mansoni viability based on the tetrazolium salt XTT

Abstract: Background Schistosoma mansoni is a trematode parasite that causes schistosomiasis, one of the most prevalent neglected tropical diseases, leading to the loss of 2.6 million disability-adjusted life years. Praziquantel is the only drug available, and new drugs are required. The most common strategy in schistosomiasis drug discovery is the use of the schistosomula larval-stage for a pre-screen in drug sensitivity assays. However, assessing schistosomula viability by microscopy has always been a limitation to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…ATP and NAD(P) metabolic indicators, DNA intercalation agents such as propidium iodide, and visual- or automated image-based systems) and readouts (e.g. percentage death, EC 50 value or phenotypic score), have been developed such that the general interpretability of data may be constrained by the particular assay employed [911, 24, 28, 3234].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP and NAD(P) metabolic indicators, DNA intercalation agents such as propidium iodide, and visual- or automated image-based systems) and readouts (e.g. percentage death, EC 50 value or phenotypic score), have been developed such that the general interpretability of data may be constrained by the particular assay employed [911, 24, 28, 3234].…”
Section: Resultsmentioning
confidence: 99%
“…XTT (sodium-2,3-bis-[2-methoxy-4-nitro-5-sulfophenyl]-2H–tetrazolium-5-carboxanilide) was used as an indicator of schistosomula metabolic activity by the reduction of the yellow tetrazolium salt XTT to an orange formazan product [28, 29]. XTT was dissolved in Medium 199 without FBS to prepare a 1 mg/ml solution and the electron coupling reagent, N-methyl dibenzopyrazine methyl sulfate (PMS; Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Plate readers have a significant cost, and the additional requirement for black-sided microplates designed for fluorescence assays increases the overall cost of the assays. Some studies found that simpler, less advanced machines could not measure the fluorescence accurately enough when quantifying schistosomula viability [6,16]. The assays should therefore be verified for cercariae using less-advanced plate readers, e.g.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The change in the dye's intensity can be used to quantify the sample's viability (visually under a microscope, or automated using spectrophotometers, flow cytometers or plate readers) [8]. These methods have significant advantages in terms of standardization, accuracy, simplicity of experiments, and replicability [16]. Fluorescence and colorimetric assays for determining parasite viability have been reviewed by Keiser [15] and Peak and Hoffmann [8], and although some of these methods have been shown to work on part of the schistosome lifecycle (for example MTT formazan on adult worms [17,18] or methylene blue on schistosomula [19]), there is a need to develop high-throughput assays for detecting cercarial viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation